The Role Of Paternalistic Leadership Dimensions On Employee Innovation Work Behavior - Nita Julita; Sri Wartini (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This study aims to examine the influence of paternalistic leadership dimensions (benevolent leadership, moral leadership and authoritarian leadership) on innovation work behavior which has an important role as a driver of resource management in organizations to build innovative employee work behavior. The population of this study were employees of Investment Office and One-Stop Integrated Services Semarang Regency with sample techniques using saturated samples of 40 people and statistical analysis tools using Smart PLS Version 4.0. The results showed that the hypothesis that states the role of paternalistic leadership dimensions such as benevolent leadership and authoritarian leadership has an effect on innovation work behavior is accepted, while moral leadership has an effect on innovation work behavior is not accepted. Suggestions for future research should add or combine with other predictor variables so that the study can be generalized such as transformational leadership, transactional leadership, and work environment to improve innovation work behavior.